Características e monitoramento do tapering no triathlon: uma revisão sistemática - Buck, K. H.; Braz, T. V.; Vilela Junior, G. B.; Lopes, C. R. (Revista Brasileira de Ciência e Movimento, 2017)
Tapering is the time of periodization when training load is reduced in order to lower the physiological, biomechanical and psychological stress thus leading to an improved performance. This paper aims to present and discuss the characteristics and monitoring of taper in triathlon. According to the established search criteria, 7 papers were found. Current evidence show that volume training should be lowered in 41% to 60% for swimming and 21% to 60% for cycling and running in the tapering for trained triathletes. Training intensity must be maintained during rapid exponential fall mode taper. It should last from 8 to 14 days for running and cycling and 21 days for swimming. The pre tapering period determines the magnitude of tapering results, and a 3% performance increase is expected in the competition.